Effect of Aerobic Exercise on Improving Symptoms of Individuals With Schizophrenia: A Single Blinded Randomized Control Study - Wang, Peng-Wei; Lin, Huang-Chi; Su, Chwen-Yng; Chen, Ming-De; Lin, Kuo C.; Ko, Chih-Hung; Yen, Cheng-Fang (Frontiers in Psychiatry, 2018)
Introduction Antipsychotic treatment can improve the symptoms of schizophrenia; however, residual symptoms after antipsychotic treatment are frequent. The effects of exercise on the symptoms of schizophrenic patients under antipsychotic treatment are not conclusive. The aim of this randomized case–control study was to examine the effects of aerobic exercise (AE) on the symptoms of schizophrenic patients receiving antipsychotic treatment. Method In total, 33 and 29 participants who received antipsychotics for schizophrenia were randomly assigned into intervention and control groups, respectively. We measured the severities of schizophrenic symptoms using the Chinese version of the Positive and Negative Syndrome Scale (PANSS) before, immediately after, and at 3 months after the intervention in both the AE and control groups. Results In total, 24 participants (72.7%) in the AE group and 22 participants (75.9%) in the control group completed the study. The results indicated that the severities of positive symptoms and general psychopathology in the AE group significantly decreased during the 12 weeks of intervention but did not further significantly change during the follow-up period of 3 months. The severity of negative symptoms in the AE group significantly decreased after 12 weeks of intervention and continued decreasing during the 3-month follow-up period. Interaction effects between time and group for the severities of symptoms on the negative and general psychopathology scales were observed. Conclusion AE can improve the severities of symptoms on the negative and general psychopathology scales in individuals with antipsychotic-treated schizophrenia.